Civil Servants and Non-Western Migrants’ Perceptions on Pathways to Health Care in Serbia—A Grounded Theory, Multi-Perspective Study - Buch Mejsner, Sofie; Kristiansen, Maria; Eklund Karlsson, Leena (International journal of environmental research and public health, 2021)
(1) Background: Informal patient payments continue to persist in the Serbian health care system, exposing vulnerable groups to private spending on health care. Migrants may in particular be subject to such payments, as they often experience barriers in access to health care. Little is known about migrants paying informally to access health care in Serbia. The study aims to explore pathways of accessing health care, including the role of informal patient payments, from the perspectives of civil servants and non-western migrants in Serbia. (2) Methods: Respondents (n = 8 civil servants and n = 6 migrants) were recruited in Belgrade in 2018, where semi-structured interviews were conducted. The interviews were analysed applying the grounded theory methodological steps. (3) Results: Data reveal different pathways to navigate the Serbian health care system, and ultimately whether paying informally occurs. Migrants appear less prone to paying informally and receive the same or better-quality health care. Locals experience the need to pay informal patient payments, quasi-formal payments and to bring medicine, materials or equipment when in health facilities. (4) Conclusions: Paying informally or using private care in Serbia appear to have become common. Despite a comprehensive health insurance coverage, high levels of out-of-pocket payments show barriers in accessing health care. It is highly important to not confuse the cultural beliefs with forced spending on health care and such private spending should be reduced to not push people into poverty.